PENGARUH PENGALAMAN, DAN SKEPTISME BAGI AUDITOR DI DALAM MENDETEKSI ADANYA RED FLAGS PADA SUATU TINDAK KECURANGAN LAPORAN KEUANGAN - Gunawan Lesmana; Bintang Hari Yudhianti; S, Patricia Febrina Dwijayanti (Jurnal Akuntansi Kontemporer, 2020)
Auditor as an independent party has an obligation to examine the company’s financial statements and stated that the fi-nancial statements are reasonable, but in carrying out the duties required expertise to identify the presence or absence of red flags so some fraud could be revealed and not mislead the users of the financial statements. This study aimed to investigate the effect of auditor’s experience and the level of auditor’s scepticism towards red flags in detecting the presence of a fraudulent financial statement. The population used in this study are all external auditors who worked on PAO(Public Accountant office) in Surabaya. The sampling technique using convenience sampling and purposive sampling, and the number of samples in this study were 45 respondents. The data comes from a questionnaire distributed to the external auditors who worked on PAO in Surabaya. Data were analyzed using multiple linear regression analysis. The results of this study indicate that there is a positive effect of variable levels of auditor’s experience and the auditor’s skepticism towards red flags.